Factors predicting normal visual acuity following anatomically successful macular hole surgery. Issue 3 (24th August 2020) - Fallico, Matteo; Jackson, Timothy L.; Chronopoulos, Argyrios; Hattenbach, Lars‐Olof; Longo, Antonio; Bonfiglio, Vincenza; Russo, Andrea; Avitabile, Teresio; Parisi, Francesca; Romano, Mario; Fiore, Tito; Cagini, Carlo; et al.
Abstract: Purpose: To assess the incidence of normal vision following anatomically successful macular hole surgery and associated clinical variables. Methods: Multicentre, retrospective chart review. Preoperative, intraoperative and postoperative clinical data were extracted from electronic medical records from seven European vitreoretinal units. Inclusion criteria were as follows: eyes undergoing primary vitrectomy for idiopathic full‐thickness macular hole from January 2015 to January 2018; postoperative macular hole closure confirmed by spectral domain optical coherence tomography (OCT); preoperative pseudophakia or phakic eyes receiving combined cataract surgery; one‐year follow‐up. The primary outcome was 'normal vision' defined as a final best‐corrected visual acuity (BCVA) ≥ 20/25. Univariate, multivariate and decision‐tree analyses were conducted to evaluate the clinical variables associated with 'normal vision'. Odds ratios (OR) and confidence intervals (CIs) were calculated. Results: Of 327 eligible cases, 91 (27.8%) achieved 'normal vision' at 1 year. Multivariate analysis identified variables significantly associated with 'normal vision': shorter symptom duration (odds ratio [OR]=1.05; 95% confidence interval [CI]:1.02‐1.09; p = 0.002), smaller preoperative OCT minimum linear diameter (OR per 100‐micron increase = 1.65; 95%CI:1.31‐2.08; p < 0.001) and better mean preoperative BCVA (OR = 15.13; 95%CI: 3.59‐63.65; p < 0.001). The decision‐tree analysis found that the most significant variable associated with 'normal vision' was symptom duration. 'Normal vision' was achieved in 70.6% of eyes operated within one week from symptom onset and in 45% of eyes with symptom duration between 1 and 3 weeks. Conclusions: These findings suggested urgent surgery is justified for small macular holes of short duration.